2017
DOI: 10.1186/s40478-017-0438-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus due to multiple ependymal malformations is caused by mutations in the MPDZ gene

Abstract: Congenital hydrocephalus is considered as either acquired due to haemorrhage, infection or neoplasia or as of developmental nature and is divided into two subgroups, communicating and obstructive. Congenital hydrocephalus is either syndromic or non-syndromic, and in the latter no cause is found in more than half of the patients. In patients with isolated hydrocephalus, L1CAM mutations represent the most common aetiology. More recently, a founder mutation has also been reported in the MPDZ gene in foetuses pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 31 publications
(39 reference statements)
0
45
0
Order By: Relevance
“…The first reported MPDZ mutation linked to severe congenital hydrocephalus in humans would have truncated 12 of the 13 PDZ domains (Al‐Dosari et al , ). A subsequent study reported three new mutations that caused truncation of MPDZ within PDZ domain #3, a frameshift within PDZ domain #1, and a truncation within PDZ domain #5 (Saugier‐Veber et al , ). All three mutations were expected to introduce a premature stop codon and result in nonsense‐mediated decay of the transcript.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first reported MPDZ mutation linked to severe congenital hydrocephalus in humans would have truncated 12 of the 13 PDZ domains (Al‐Dosari et al , ). A subsequent study reported three new mutations that caused truncation of MPDZ within PDZ domain #3, a frameshift within PDZ domain #1, and a truncation within PDZ domain #5 (Saugier‐Veber et al , ). All three mutations were expected to introduce a premature stop codon and result in nonsense‐mediated decay of the transcript.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent gene linked to congenital hydrocephalus is MPDZ , encoding a large modular scaffold protein that consists of 13 PDZ domains and one L27 domain (Ullmer et al , ; Adachi et al , ). Several cases of severe congenital hydrocephalus identified in five consanguineous families (Al‐Dosari et al , ; Saugier‐Veber et al , ) were linked mostly to biallelic nonsense mutations that resulted in nonsense‐mediated decay and total loss of MPDZ. A milder phenotype in a non‐consanguineous family was linked to missense mutations and a heterozygous splice site variant (Al‐Jezawi et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, variants in human MPDZ gene suggest a possible association with alcohol dependence (Karpyak et al, 2009). Variants in MPDZ have also been associated with congenital hydrocephalus, a neuropathy (Feldner et al, 2017;Saugier-Veber et al, 2017).…”
Section: Orthologous Pdelvarsmentioning
confidence: 99%
“…Their function is not yet annotated and should be investigated in the future. Saugier-Veber et al (2017) reported that MPDZ gene is a component of tight junctions, which are expressed from early brain development in choroid plexuses and ependyma.…”
Section: Orthologous Pdelvarsmentioning
confidence: 99%